On robustness for natural language processing - La Malfa, E (2023)
As a discipline, machine learning has contributed to significant breakthroughs in Natural Language Processing (NLP), aiming to design algorithms to manipulate text and produce insights, such as classification and summarization, comparable to those of humans. Natural language poses challenges that reflect peculiarities of human intelligence, such as grasping the meaning of a sentence or preserving long-term relationships between words that possibly appear distant from each other.